Validation of a self-report questionnaire addressing antisocial behavior in adolescents: CACSA - Bañares, Paula Alarcón (2010)
This paper reports the validation of a rationally built self-report instrument to assess social behavior in Chilean adolescents (CACSA) and presents the findings on social behavior from two samples: school attending adolescents (N=1914) and juvenile offenders (N=264). The questionnaire consists of 56 items, which explore three general behavioral dimensions: Prosocial (CPRO) and Antisocial (CAT) behavior, and Victims of Abuse of Power (VAP); CAT contains six specific dimensions: Crimes (D), Transgressions Against Property (TPRO), Transgressions Against Persons (TPER); Abusive Behavior with Peers (CAP), Substance Abuse (OHD); and Minor Social Transgressions (TSL). The study also includes a social desirability scale and an attitudinal scale. Results revealed the questionnaire has important psychometric strengths, as well as discriminative properties between the school attending adolescents and the juvenile offenders. The importance and reliability of self-report data for building indices of antisocial behavior is discussed, as well as the relationship between prosocial and antisocial behavior among Chilean adolescents.El estudio tiene por objetivo presentar la validación de un instrumento formulado racionalmente para evaluar, mediante auto-reporte, el comportamiento social en adolescentes chilenos (CACSA) y describir el comportamiento social de dos grupos: adolescentes escolarizados (N=1914) y adolescentes infractores de ley (N=264). El cuestionario posee 56 ítemes que exploran tres dimensiones generales, a) Comportamiento Prosocial (CPRO), b) Comportamiento Antisocial Total (CAT); y c) Víctima de Abuso de Poder (VAP); CAT contiene seis dimensiones específicas: Delitos (D), Transgresiones Contra la Propiedad (TPRO), Transgresiones Contra las Personas (TPER), Comportamiento Abusivo con Pares (CAP), Consumo de Alcohol y Drogas (OHD); y Transgresiones Sociales Leves (TSL). El estudio incluye también una escala de deseabilidad social y otra actitudinal. Los resultados revelan importantes fortalezas psicométricas del instrumento y capacidad de discriminación entre adolescentes escolarizados e infractores de ley. Se discute la importancia de reconocer por auto-reporte la prevalencia de comportamientos antisociales y la relación entre conductas prosociales y antisociales en adolescentes chilenos.O estudo tem por objetivos apresentar a validação de um instrumento formulado racionalmente para avaliar, mediante auto-relato, o comportamento social de adolescentes chilenos (CACSA) e descrever o comportamento social de dois grupos: adolescentes escolarizados (N=1914) e adolescentes infratores da lei (N=264). O questionário consiste de 56 itens que exploram três dimensões gerais: a) Comportamento Pró-social (CPRO), b) Anti-Social (CAT) c) Vítimas de Abuso de Poder (VAP). CAT contém seis dimensões específicas: Delitos (D), Transgressões de Ofensa à Propriedade (TPRO), Transgressões Contra as Pessoas (TPER), Comportamentos Abusivos entre Pares (CAP), Consumo do Álcool e Drogas (OHD) e Transgressões Sociais Leves (TSL). O estudo incluiu também uma escala de desejabilidade social e outra atitudinal. Os resultados revelam que o instrumento mostra excelentes qualidades psicométricas e capacidade de discriminação entre os adolescentes escolarizados e os infratores da lei. Discute-se a importância de reconhecer a prevalência de comportamentos anti-sociais por meio de auto-relato e a relação entre condutas pró-sociais e anti-sociais em adolescentes chilenos